Self-reported sleep quantity, quality and sleep hygiene in elite athletes - Knufinke, M.; Nieuwenhuys, A.; Geurts, S. A. E.; Coenen, A. M. L.; Kompier, M. A. J. (Journal of Sleep Research, 2018)
Sleep is essential for recovery and performance in elite athletes. While actigraphy-based studies revealed suboptimal sleep in athletes, information on their subjective experience of sleep is scarce. Relatively unexplored is also the extent to which athletes` sleep is adversely affected by environmental conditions and daytime behaviours, that is sleep hygiene. This study aimed to provide insight in sleep quantity, quality and its putative association with sleep hygiene. Participants were 98 elite (youth) athletes competing at the highest (inter-)national level. Sleep quantity, quality and sleep hygiene were assessed once covering a 1-month period by using established (sub)clinical questionnaires, and repeatedly during 7 consecutive days. Sleep quality was generally healthy, although 41% of all athletes could be classified as `poor sleeper`, and 12% were identified as having a sleep disorder. Daily self-monitoring revealed sleep durations of 8:11 ± 0:45 h, but elevated wake after sleep onset of 13 ± 19 min. Sleep quality, feeling refreshed, and morning vigor were moderate at best. Regarding sleep hygiene, general measures revealed irregular sleep-wake patterns, psychological strain and activating pre-sleep behaviours. At the daily level, blue-light exposure and late-evening consumption of heavy meals were frequently reported. General sleep hygiene revealed significant associations with sleep quality (0.45 < r > 0.50; P < 0.001). Results indicate that there is ample room for optimization, specifically in onset latency and in wake after sleep onset. Subtle improvements in sleep seem possible, and optimizing sleep hygiene, such as regular sleep-wake patterns and reducing psychological strain, may facilitate this sleep upgrading process.